Human genome evolution and development of cardiovascular risk factors through natural selection - Poledne, R; Zicha, J (Physiological research, 2018)
Impressive advances in molecular genetic techniques allow to analyze the effects of natural selection on the development of human genome. For example, the trend towards blonde hair and blue eyes was documented. The approach to analyze possible effects of natural selection on the evolution of recent phenotypes with high risk of cardiovascular disease has not been described yet. A possible effect on the evolution of two main risk factors - hypercholesterolemia and hypertension - is presented. The close relationship of non-HDL cholesterol blood concentration to the proportion of pro-inflammatory macrophages in human visceral adipose tissue might be a result of long-lasting natural selection. Individuals with higher proportion of this phenotype might also display a higher ability to fight infection, which was very common in human setting from prehistory until Middle Ages. Successful battle against infections increased the probability to survive till reproductive age. Similar hypothesis was proposed to explain frequent hypertension in African Americans. A long-lasting selection for higher ability to conserve sodium during long-term adaptation to low sodium intake and hot weather was followed by a short-term (but very hard) natural selection of individuals during transatlantic slave transport. Only those with very high capability to retain sodium were able to survive. Natural selection of phenotypes with high plasma cholesterol concentration and/or high blood pressure is recently potentiated by high-fat high-sodium diet and overnutrition. This hypothesis is also supported by the advantage of familial hypercholesterolemia in the 19th century (at the time of high infection disease mortality) in contrast to the disadvantage of familial hypercholesterolemia during the actual period of high cardiovascular disease mortality.
Keywords: kardiovaskulární nemoci; selekce (genetika); lidé; Selection, Genetic; riziko; Genome, Human; Risk; genom lidský; Cardiovascular Diseases; Evolution, Molecular; molekulární evoluce; Humans